Detection of biennial rhythm and estimation of repeatability in mango (Mangifera indica L.) - Choudhary, Ram Kumar; Rao, A.R.; Wahi, S.D.; Mishra, A.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Most of the perennial crops exhibit biennial rhythm in fruiting and growth. Among the perennial crops, mango is an important fruit crop not only in India but also across the world. This crop acquires bienniality, a complex phenomenon, by carrying a heavy fruiting in one year called ‘on’ year and little or no fruiting in the next year called ‘off’ year. The presence of bienniality in the data may affect genetic parameter estimates like repeatability. In this paper, the extent and intensity of bienniality in mango has been studied by graphical as well as quantitative approaches. Besides, a test of significance for bienniality has been obtained for each tree using binomial distribution. On this basis, the percentage trees in ‘on’ years and in ‘off’ years has been quantified for four different locations. Also, variety-wise biennial rhythm has been studied in these locations. The results reveal that there exists a moderate to strong bienniality in mango crop. Besides, the errors become auto-correlated when bienniality is removed by taking moving average. Moving average methods have been applied to estimate the repeatability. The results reveal that the mango yield was moderate to highly repeatable.